ANALISIS EFISIENSI EKONOMIS PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI PADI SAWAH DI KECAMATAN PEMAYUNG KABUPATEN BATANGHARI - Seprianti, Nopita; Edison, Edison; Ningsih, Rozaina (Enviagro: Jurnal Pertanian dan Lingkungan, 2023)
This research aims to: 1) Understand the general description of lowland rice farming, 2) Analyze the influence of the use of production factors on lowland rice production. This study uses primary data. The sampling method used simple random sampling method with a total of 68 farmers as respondents. The analytical method used to describe lowland rice farming in general uses descriptive qualitative analysis, while to determine the effect of the use of production factors on lowland rice production is multiple linear regression with the Cobb-Douglas production function. Based on the results of the analysis that has been carried out, it is found that lowland rice farming in Pemayung District, Batang Hari Regency is a small-scale farming activity which aims to meet daily living needs with local seeds and the use of fertilizers and pesticides which is not yet optimal. Production factors in the form of land area, seeds, urea fertilizer, pesticides and labor have a significant effect on lowland rice production. Meanwhile, the production factor in the form of NPK fertilizer had no significant effect on lowland rice production.